Concomitant Chemo-Radiotherapy with Oral Capecitabine in Locally Advanced Squamous Cell Carcinoma Cervix - Aalia Bashir, Sana Mehreen, Anis Fatima, Fakhira Jabeen, Ayesha Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cervical carcinoma is the fourth most common malignant neoplasm after carcinoma of the breast, lung, colorectal, endometrium and ovary. Aim: To assess the all RECIST responses of concomitant chemo-radiotherapy with capecitabine in locally advanced squamous cell carcinoma cervix in a tertiary healthcare facility at Multan. Methodology: It was a Descriptive case series Conducted at the Department of Clinical Oncology, Nishtar Hospital Multan. Patients (n=60) with locally advanced squamous cell carcinoma cervix received conventional radiation (Total Dose: 45Gy) with 825 mg/m2 twice daily Capecitabine for five days a week for 6 weeks and followed by brachytherapy. Data was evaluated by using SPSS version 23. Post stratification Chi-square test was applied with P-value of 0.05 was considered as significant. Results: Mean age of patient population was 39.5±6.8 (range: 31-52) years. Majority i.e. 30(50%) were between 30 to 40 years of age. The overall response rate was 88%, complete Response Rate was 80%, Partial Response rate was 8.3%, Stable Disease lasting ≥6 months was 5%, Progressive Disease was 6.7% in 60 patients at the end of treatment. Commonly observed performance status was ECOG 0 (n=57, 95.0%) while most of the patients had stage IIB at presentation (n= 35, 58.3%). Practical Implication: Current project helped health providers to evaluate response rate to cervical carcinoma treatment to oral capeccitabine. With other chemo-drugs like Cisplatin, renal toxicity developed even with single low dose as elderly patients are more susceptible. Because renal toxicity of oral capecitabine was low as compared to cisplatin thus it was more effective than cisplatin. Due to low local data regarding oral capecitabine in cervical carcinoma as treatment option so planned present study. Conclusion: It was concluded that patients of cervical carcinoma showed better response rate to concomitant chemo-radiation using Capecitabine with low renal toxicity. Keywords: Cervical Cancer, Oral Capecitabine, Concurrent Chemo-Radiation and Brachytherapy